PROSES KREATIF KUNTZ AGUS DALAM ADAPTASI NOVEL MENJADI FILM “SURGA YANG TAK DIRINDUKAN” - Nurul Muzdalifah; Fajar Aji (Institut Seni Budaya Indonesia Bandung, 2020)
ABSTRACTSurga Yang Tak Dirindukan is one of the film adaptation of the novel Surga Yang Tak Dirindukan by Asma Nadia. The film is produced by MD Entertainment in 2015 and directed by Kuntz Agus. Adaptation of two medias between the novel into a film resulted in changes in Surga Yang Tak Dirindukan film. The director could not include all the stories in the novel, so it needs ecranisation in the film, including changes, downsizing, additions, and variation of change. More dominant ecranisation happened in the aspect of the plot, story, setting, also characters and characterizations in the film adaptation. The theory used by researcher are ecranisation and creative process as the main theory, while aesthetics and subjectivity the director used as the second theory. This study focuses on the creative process undertaken by Kuntz Agus while do the ecranisation process, because the process requires consideration in many ways. Descriptive qualitative research method is used by researcher to get the result of research in the form of Surga Yang Tak Dirindukan novel and film’s ecranisation as well as the creative process by Kuntz Agus. Based on these results, researcher concluded that the creative process by Kuntz Agus more focused on the dramatic aspect and logic in building a story of the film of Surga Yang Tak Dirindukan.